2015
DOI: 10.1016/j.jes.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the size distributions of surface properties for purple soil and yellow soil

Abstract: Soils contain diverse colloidal particles whose properties are pertinent to ecological and human health, whereas few investigations systematically analyze the surface properties of these particles. The objective of this study was to elucidate the surface properties of particles within targeted size ranges (i.e. > 10, 1-10, 0.5-1, 0.2-0.5 and <0.2 μm) for a purple soil (Entisol) and a yellow soil (Ultisol) using the combined determination method. The mineralogy of corresponding particle-size fractions was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Both soil types contained aluminosilicates consisting of SiO 2 silicon–oxygen tetrahedra and Al 2 O 3 octahedra (Tang et al ., ); therefore, we consider that the van der Waals force and hydration force are approximately the same for the two soils, and thus the associated pressures (calculated from Equations and ), when added to the electrostatic repulsive pressure, provide the distributions of net pressure between two adjacent particles under different electrolyte concentrations for the each soil (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Both soil types contained aluminosilicates consisting of SiO 2 silicon–oxygen tetrahedra and Al 2 O 3 octahedra (Tang et al ., ); therefore, we consider that the van der Waals force and hydration force are approximately the same for the two soils, and thus the associated pressures (calculated from Equations and ), when added to the electrostatic repulsive pressure, provide the distributions of net pressure between two adjacent particles under different electrolyte concentrations for the each soil (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…the aggregation of separate particles). Let us bear in mind that particles with diameters of < 1 μm contribute 76.1% of the surface charges and 71.6% of the surface area of the soil used in our study (Tang et al ., ). Therefore, these results might differ from those for soils that contain mainly coarse particles, but they may be applicable generally to clay‐rich soil.…”
Section: Discussionmentioning
confidence: 97%
“…Soil particles of < 10‐μm diameter accounted for 63.7% of the total soil mass and those < 1 μm accounted for 57%. Particles < 1‐μm diameter contributed to 76.1% of surface charges and 71.6% of surface area of the soil (Tang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Therefore, the contents of fine colloids have been observed to be variable in the paddy soils derived from different upland soils (Chen et al., 2011; Jiang et al., 2017; Z. P. Li et al., 2005; Z. Zhao et al., 2019). On the other hand, soil surface charge is mainly determined by the fine colloids, due to their relatively large specific surface area and the high density of their reactive surface sites (Y. Tang et al., 2015). In contrast to the numerous studies on the surface properties of bulk Anthrosols and their corresponding parental, upland soils, particularly the content of fine colloidal fractions (Nguyen et al., 2009), few reports have been published comparing the surface properties of specific‐sized particles from upland soils and Anthrosols, the particle size distributions (PSD) of which are more susceptible to variation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have also shown that the surface electrochemical properties of soil particles change markedly as their particle size decreases to the nanoscale (W. Li et al., 2012; Qafoku, 2010; Y. Tang et al., 2015). In addition, the phenomenon of flocculation, caused by interactions among soil particles, is the first step necessary for the formation of soil structure.…”
Section: Introductionmentioning
confidence: 99%